Cloud point extraction of vanadium in parenteral solutions using a nonionic surfactant (PONPE 5.0) and determination by flow injection-inductively coupled plasma optical emission spectrometry - Wuilloud, Gustavo M. (2002)
A preconcentration and determination methodology for vanadium at trace levels in parenteral solutions was developed. Cloud point extraction was successfully employed for the preconcentration of vanadium prior to inductively coupled plasma atomic optical emission spectrometry (ICP-OES) coupled to a flow injection (FI) system. The vanadium was extracted as vanadium-2-(5-bromo-2-pyridylazo)-5-diethylaminophenol [V-(5-Br-PADAP)] complex, at pH 3.7 mediated by micelles of the nonionic surfactant polyoxyethylene (5.0) nonylphenol (PONPE 5.0). The extracted surfactant-rich phase (100 μl) was mixed with 100 μl of ethanol and this final volume injected into ICP-OES for the vanadium determination. Under these conditions, the 50 ml sample solution preconcentration allowed raising an enrichment factor of 250-fold; however, it was possible to obtain a theoretical enrichment factor of 500-fold. The lower limit of detection (LOD) obtained under the optimal conditions was 16 ng 1-1. The precision for 10 replicate determinations at the 2.0 μg-1 V level was 2.3% relative standard deviation (RSD), calculated with the peak heights. The calibration graph using the preconcentration system for vanadium was linear with a correlation coefficient of 0.9996 at levels near the detection limits up to at least 50 μg 1-1. The method was successfully applied to the determination of vanadium in parenteral solution samples.